2005
DOI: 10.1007/s11284-005-0107-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the ecological conditions on morphological variations of the green toad, Bufo viridis, in Turkey

Abstract: Ten populations of the green toad, Bufo viridis, from three areas having different climatic regimes were compared. Multivariate analyses of morphological characteristics revealed three distinct populations of green toads: the first group inhabiting the lowland and humid localities was characterized by a small body size, the second group occurred at higher altitudes and in desert areas had a significantly larger body size, while the third group from the Mediterranean localities was characterized by a large tymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 12 publications
2
9
0
Order By: Relevance
“…, 1999; Castellano, Giacoma & Dujsebayeva, 2000; Rosso et al. , 2004; Schäuble, 2004; Kutrup et al. , 2006; Lougheed et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, 1999; Castellano, Giacoma & Dujsebayeva, 2000; Rosso et al. , 2004; Schäuble, 2004; Kutrup et al. , 2006; Lougheed et al.…”
Section: Discussionmentioning
confidence: 99%
“…A candidate for such process could be climate‐provoked phenotypic variation. Climatic conditions as an important agent influencing animal morphology have been documented in many ectothermic and endothermic animals (Rosso, Castellano & Giacoma, 2004; Schäuble, 2004; Davis, 2005; Kutrup, Bulbul & Yilmaz, 2006). Convergent emergence of ecomorphs during iterative climatic cycles suggests a strong potential of climatic conditions to form similar phenotypes even among distantly‐related animals (Martin & Meehan, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Morphometric multivariate analyses in Baldissera et al (2004) show that most of the variation in the group is associated with this variable, raising the possibility that size acted as a confounding factor in the morphometric analyses that may otherwise support taxonomic decisions for the group. Furthermore, morphometric studies on anurans have reported variation that covaries with variation in environmental conditions (Castellano & Giacoma, 1998;Castellano et al, 1999;Rosso, Castellano & Giacoma, 2004;Schauble, 2004;Kutrup, Bulbul & Yilmaz, 2006;Marcelino, Haddad & Alexandrino, 2009), raising the possibility that local climates might also play a role in generating phenotypic differentiation within the R. crucifer group.…”
Section: Introductionmentioning
confidence: 99%
“…These parapatric species were differentiated mainly by adult size, crest development, and skin texture. All these characters have been demonstrated to be subject to variation due to specific environmental conditions throughout the distribution of some bufonids (see Kutrup et al, 2006;Bandeira et al, 2016). Thus, we consider Rhinella paraguayensis Ávila et al, 2010, to be a junior synonym of R .…”
Section: Percentage Of Uncorrected P-distances Between 16s Sequences Among Species Of the Rhinella Veraguensis Groupmentioning
confidence: 88%
“…alata by several characters such as its larger size, presence of welldeveloped cranial crests, vertebral apophysis, and bony knob (Mijares-Urrutia and Arends, 2001;Santos et al, 2015), although these characters vary extensively within species of the R . margaritifera Group and might be associated with particular environmental conditions over their areas of distribution (see Kutrup et al, 2006;Bandeira et al, 2016). The absence of evident differences between specimens of both clades of R .…”
Section: Percentage Of Uncorrected P-distances Between 16s Sequences Among Species Of the Rhinella Veraguensis Groupmentioning
confidence: 99%